1978
DOI: 10.1177/036354657800600615
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of stress fractures

Abstract: It is felt that stress fractures are caused by excessive, repetitive muscle forces acting across the affected bone. These fractures should be suspected in participants of athletic endeavors who present with a history of persistent, focal, activity-related pain regardless of their stage of physical conditioning. Associated physical findings are localized tenderness and swelling without evidence of a generalized systemic response. Bone scans and serial roentgenograms including specialized views may be required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
1
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(63 citation statements)
references
References 19 publications
0
59
1
3
Order By: Relevance
“…These figures must be seen in light of the fact that in four of these cases (all cases being located in the tibia), the initial treatment plan provided for the reduction of weightbearing on the extremity affected and the treatment was (2), while in those engaged in endurance sports (1) fractures in the metatarsal bones are most frequent. Only one patient engaged in a type of sport (bicycling) with little increased biomechanical stress on the lower extremity (3) switched to immobilization in a plaster cast because symptoms persisted. In one case-that of a tennis player with a fatigue fracture in the region of the olecranon-internal fixation with kirschner wires was carried out because there was a threat of dislocation, and the implant material was removed after 6 months, by the time a good clinical result of the treatment had been achieved.…”
Section: Therapy and Results Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These figures must be seen in light of the fact that in four of these cases (all cases being located in the tibia), the initial treatment plan provided for the reduction of weightbearing on the extremity affected and the treatment was (2), while in those engaged in endurance sports (1) fractures in the metatarsal bones are most frequent. Only one patient engaged in a type of sport (bicycling) with little increased biomechanical stress on the lower extremity (3) switched to immobilization in a plaster cast because symptoms persisted. In one case-that of a tennis player with a fatigue fracture in the region of the olecranon-internal fixation with kirschner wires was carried out because there was a threat of dislocation, and the implant material was removed after 6 months, by the time a good clinical result of the treatment had been achieved.…”
Section: Therapy and Results Of Treatmentmentioning
confidence: 99%
“…In most studies, any patients with an immature skeletal system are just regarded as a subgroup of the overall patient population and not considered separately at all [3,8,[12][13][14][15][16]. Additionally, the population in these studies is heterogenous, as it includes athletes, patients with biomechanical abnormalities (i.e., patients with clubfoot) and even patients with ICP [17].…”
mentioning
confidence: 99%
“…In contrary Wagner et al [8] showed that the anterior aspect of the midshaft of the tibia is an area under tension than compression. Stanitsky et al [9] believes that concentrated muscle forces acting across a specifi c bone enhance the loading which occurs simply from direct weightbearing thus anterior cortex fractures of the tibia may be due to additional forces from the posterior muscle group causing increased anterior tension stress. As a consequence these lesions appear to be prone to delayed union or non union.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators believe that muscles produce large strains in bone, especially at the muscle attachment points (29). This could potentially contribute to the occurrence of stress fractures in the upper body, such as at the ribs during rowing (25) and golfing (24), or in the humerus during throwing (23).…”
Section: Intrinsic Risk Factorsmentioning
confidence: 99%